External validation of the Candiolo nomogram for high-risk prostate cancer patients treated with carbon ion radiotherapy plus androgen deprivation therapy: a retrospective cohort study. (23rd April 2022) - Utsumi, Takanobu; Suzuki, Hiroyoshi; Ishikawa, Hitoshi; Hiroshima, Yuichi; Wakatsuki, Masaru; Harada, Masaoki; Ichikawa, Tomohiko; Akakura, Koichiro; Tsuji, Hiroshi
Abstract: The aim of this study was to reclassify high-risk prostate cancer patients treated with carbon-ion radiotherapy and androgen deprivation therapy using the Candiolo nomogram and evaluate usefulness to predict the following 10-year biochemical recurrence. Six hundred seventy-two high-risk prostate cancer patients were reclassified according to the Candiolo nomogram. The cumulative incidence curves for biochemical recurrence were compared by Gray's test. Furthermore, five predictors of the Candiolo nomogram in our patients were evaluated by Fine and Gray regression hazards model. The higher the Candiolo risk, the worse the biochemical recurrence, especially in high- and very high-risk patients. Out of five predictors, age ≥70 years, cT3 stage, biopsy Gleason score ≥9 or the percentage of positive biopsy cores ≥50% had significant impacts on 10-year biochemical recurrence in our patients. The Candiolo nomogram can reclassify our high-risk prostate cancer patients treated with carbon-ion radiotherapy and androgen deprivation therapy and evaluate the biochemical recurrence preciously. Abstract : We reclassified high-risk prostate cancer patients treated with carbon-ion radiotherapy and androgen deprivation therapy using the Candiolo nomogram. The Candiolo nomogram can evaluate the biochemical recurrence preciously in our high-risk prostate cancer patients.